The corporate financiers : Williams, Modigliani, Miller, Coase, Williamson, Alchian, Demsetz, Jensen, Meckling /: Williams, Modigliani, Miller, Coase, Williamson, Alchian, Demsetz, Jensen, Meckling. (2014) - Read, Colin, 1959-
No abstract available